TOURISM VILLAGE DEVELOPMENT STRATEGY BASED ON LOCAL RESOURCES IN AYUNAN VILLAGE, ABIANSEMAL DISTRICT, BADUNG REGENCY - Susila, I Putu; Sumantra, I Ketut; Sudiana, A.A; Pandawani, Ni Putu (International Journal of Research -GRANTHAALAYAH, 2021)
Ayunan Village has a variety of tourism potentials, which are worthy of being developed as an attractive tourist destination in the future. To achieve this, an appropriate management strategy is needed to develop the tourist area of the Ayunan village. The objective of this research was: 1) Exploring and assessing local resources in Ayunan village, 2) Identify and analyze community perceptions about the development of tourist villages, 3) Formulating a local resource-based tourism village development strategy. The research method was used observation, interviews, and questionnaires. SWOT analysis is used to determine the tourism village development strategy and Quantitative Strategic Planning Matrix (QSPM) analysis was used to rank development priorities. There are eight alternative strategies to develop Ayunan village as a tourist destination: a) Destination planning, b) Development of tourist attractions, c) Development of tourist facilities, d) Travel promotion or marketing, e) Community approach, f) Mapping tourism potential, g) Establishment of Tourism village community groups, h) Increase in human resources. The priority strategies base on QSPM analysis were: rank 1st was marketing or promoting. The Rank 2st Approach to the community to participate in supporting the development of tourism villages. Rank 3st Planning tourist destinations and rank 4th were increasing human resources.